Indigenous Endophytic Bacteria Potentials to Control Black Rot Disease on Cabbage Towards the Development of Organic Vegetables - Santoso, Verisca Agil Winanda; Ramadhani, Fatchuliani Safitri; Apriyani, Aliffia Nuraita; Aini, Luqman Qurata (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Organic farming plays an important role in achieving SDGs 2030, especially on point 2, 3, 13 and 15. Nevertheless, agriculture commodity often meets challenges in organic farming due to plant pests, for instance: on cabbage. Black rot disease on cabbage causes serious losses up to 70%. Most of farmers use chemical pesticides which leads to lots of negative impact towards the environment. Thus, its essential to control the environmentally friendly by applying bio control agents of indigenous endophyte bacteria instead. This article was aimed to examine the indigenous endophyte bacteria ability which excellences on organic cabbage as well as generating black rot caused by the bacterial pathogen X. campestris. Narrative reviews along was done through finding out the related material from International Journal articles. The result showed that there were indigenous endophyte bacteria which was able to be bio control agents towards black rot disease on cabbage, namely Pseudomonas fluorescens, Bacillus subtilis, and Streptomyces sp with effectivity level between 37-63% within resistance zone 1.44 up to 2.4 cm. Indigenous endophyte bacteria on organic cabbage had various kinds antagonist agents especially on Bacillus sp. and Pseudomonas sp. that able to resist the disease pathogen both in vitro and in vivo.